Alignment of magnetic particles in anisotropic Nd–Fe–B bonded magnets. (28th May 2021) - Liu, X B; Gandha, Kinjal; Nlebedim, I C; Paranthaman, M Parans
Abstract: High-performance anisotropic bonded magnets need a high volumetric filling fraction of magnetic powder in a polymer binder and good alignment while possessing adequate mechanical properties. The correlation between the degree of alignment (DOA) and the volumetric filling fraction of magnetic powder, the type of binder and the processing parameters have been studied using Nd–Fe–B anisotropic bonded magnets. Thermomagnetic analysis and differential scanning calorimetry results show that the magnetic powder can be well aligned in a bonded magnet under an external magnetic field at a temperature higher than the binders' melting point by 20–60 K, depending on the type of magnetic powder and binder. The DOA results mainly from the interplay between the Zeeman energy ( E app ) and the inter-particle static energy ( E stat ) in bonded magnets at the chosen alignment temperature and the magnetic fields. A good alignment can be achieved by an alignment magnetic field which is about twice its coercivity in an anisotropic Nd–Fe–B bonded magnet, which is confirmed by our experimental and modeling results.